Ferritic stainless steel and its manufacturing method
A ferritic stainless steel with a tailored composition and an Al-based oxide film thickness of 8-20 nm addresses the issue of low brazing properties in existing ferritic stainless steels, achieving enhanced oxidation resistance and brazing performance for high-temperature applications.
Patent Information
- Application Number
- JP2023566271
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-12-09
- Filing Date
- 2022-12-01
- Publication Date
- 2025-05-01
- Estimated Expiration
- 2042-12-01
AI Technical Summary
Existing ferritic stainless steels exhibit low brazing properties despite having effective oxidation resistance, which is a concern for applications like catalyst carriers that require both properties.
A ferritic stainless steel with a specific composition (C: 0.030% or less, Si: 0.01-1.5%, Mn: 0.01-1.00%, P: 0.050% or less, S: 0.005% or less, Cr: 15.0-25.0%, Al: 2.0-4.0%, Ni: 1.00% or less, Nb: 0.01-0.70%, N: 0.030% or less, B: 0.0003-0.01%, REM: 0.01-0.20%) and an Al-based oxide film thickness of 8 nm or more but less than 20 nm, which enhances both oxidation resistance and brazing properties.
The proposed ferritic stainless steel achieves superior oxidation resistance and brazing properties compared to conventional materials, making it suitable for high-temperature applications.
Smart Images

Figure 0007671367000004 
Figure 0007671367000001 
Figure 0007671367000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a ferritic stainless steel and a method for producing the same. [Background technology]
[0002] High-Al-content ferritic stainless steels have high-temperature oxidation resistance and are therefore widely used in a variety of heat-resistant applications, such as catalyst carriers (including electrically heated types) for purifying exhaust gases mounted on automobiles and motorcycles, plants, and combustion towers.
[0003] Patent Document 1 discloses that when the thickness of the oxide film of the Al2O3 columnar crystal is 0.1 μm or more and 1.0 μm or less, an Fe-Cr-Al alloy foil that exhibits sufficient oxidation resistance and high-temperature deformation resistance can be produced.
[0004] Patent Document 2 discloses that when the thickness of the Al2O3 film is 20 nm or more and 200 nm or less, a stainless steel foil having excellent diffusion bonding properties and brazing properties can be produced. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Publication No. 2003-105506 [Patent Document 2] Japanese Patent Application Publication No. 2011-32524 Summary of the Invention [Problem to be solved by the invention]
[0006] However, while the techniques disclosed in Patent Documents 1 and 2 are considered to be effective in terms of oxidation resistance, there is a problem in that the brazeability is low when the techniques are applied to products that require brazeability, such as catalyst carriers.
[0007] An object of one aspect of the present invention is to provide a ferritic stainless steel that has oxidation resistance and brazeability superior to conventional ones. [Means for solving the problem]
[0008] In order to solve the above problems, a ferritic stainless steel according to one embodiment of the present invention contains, by mass%, C: 0.030% or less, Si: 0.01 to 1.5%, Mn: 0.01 to 1.00%, P: 0.050% or less, S: 0.005% or less, Cr: 15.0 to 25.0%, Al: 2.0 to 4.0%, Ni: 1.00% or less, Nb: 0.01 to 0.70%, N: 0.030% or less, B: 0.0003 to 0.01%, REM: 0.01 to 0.20%, with the remainder being Fe and unavoidable impurities, and has an Al-based oxide film of 8 nm or more and less than 20 nm on the surface.
[0009] Further, a method for producing a ferritic stainless steel according to one embodiment of the present invention is a method for producing a ferritic stainless steel containing, by mass%, C: 0.030% or less, Si: 0.01 to 1.5%, Mn: 0.01 to 1.00%, P: 0.050% or less, S: 0.005% or less, Cr: 15.0 to 25.0%, Al: 2.0 to 4.0%, Ni: 1.00% or less, Nb: 0.01 to 0.70%, N: 0.030% or less, B: 0.0003 to 0.01%, REM: 0.01 to 0.20%, and the balance being Fe and unavoidable impurities, A cold rolling step and a final annealing step after the cold rolling step, The final annealing step includes a first step of heating to a temperature range of 900°C to 1200°C under an inert gas atmosphere and a dew point of -40°C or lower. Effect of the Invention
[0010] According to one aspect of the present invention, it is possible to realize a ferritic stainless steel having oxidation resistance and superior brazability to conventional stainless steels. [Brief description of the drawings]
[0011] [Figure 1] 1 is a SEM photograph showing a cross section of an alumina layer mainly made of alumina that is formed when a ferritic stainless steel according to one embodiment of the present invention is heated at 1050° C. for 50 hours. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present invention will be described in detail. In this specification, the term "stainless steel" refers to a stainless steel material whose specific shape is not limited. Examples of this stainless steel material include steel plates, steel pipes, and bar steel. In this specification, "%", which is the unit of content of each component element, means "mass %" unless otherwise specified. In addition, in this application, "A to B" indicates A or more and B or less.
[0013] (Composition of ferritic stainless steel) First, the essential elements constituting the ferritic stainless steel in this embodiment will be described.
[0014] A ferritic stainless steel according to one embodiment of the present invention has a steel component composition, in mass%, of C: 0.030% or less, Si: 0.01 to 1.5%, Mn: 0.01 to 1.00%, P: 0.050% or less, S: 0.005% or less, Cr: 15.0 to 25.0%, Al: 2.0 to 4.0%, Ni: 1.00% or less, Nb: 0.01 to 0.70%, N: 0.030% or less, B: 0.0003 to 0.01%, and REM: 0.01 to 0.20%.
[0015] In this composition, the Al content is reduced compared to conventional high-Al-content ferritic stainless steels. Since the ferritic stainless steel according to one embodiment of the present invention has the above composition, it is possible to obtain a ferritic stainless steel having excellent toughness.
[0016] The significance of the content of each element contained in the ferritic stainless steel according to an embodiment of the present invention will be described below. Note that the ferritic stainless steel consists of iron (Fe) or a small amount of impurities inevitably mixed therein (inevitable impurities) except for the following components.
[0017] <C: Carbon> C is an essential element in the ferritic stainless steel according to an embodiment of the present invention. On the other hand, as the content of C increases, abnormal oxidation is likely to occur. Further, if C is contained excessively, the toughness of the slab and the hot coil deteriorates, and it becomes difficult to process into a sheet material by hot working. Therefore, in one aspect of the present invention, the upper limit of the content of C is defined as 0.030%. When the content of C is 0.020% or less, the possibility of abnormal oxidation occurrence can be further reduced, and the workability can be improved. In view of the above reasons, a more preferable content of C is 0.002 to 0.015%.
[0018] <Si: Silicon> Si is an element effective for improving oxidation resistance and is an essential element in the ferritic stainless steel according to an embodiment of the present invention. On the other hand, if Si is contained excessively, there is a possibility of reducing toughness and workability. Therefore, in one aspect of the present invention, the content of Si is 0.01 to 1.50%. By setting the content of Si to 0.01 to 1.0%, more preferably 0.01 to 0.50%, the effect as a deoxidizer and the workability are further improved.
[0019] <Mn: Manganese> Mn is an essential element in the ferritic stainless steel according to an embodiment of the present invention. On the other hand, if Mn is contained excessively, the ferrite phase may be destabilized and the high-temperature oxidation resistance may be reduced. Therefore, in one aspect of the present invention, the content of Mn is 0.01 to 1.00%. By setting the content of Mn to 0.01 to 0.80%, more preferably 0.01 to 0.50%, the possibility of the occurrence of corrosion initiation points is further reduced.
[0020] <P: Phosphorus> P is an essential element in the ferritic stainless steel according to an embodiment of the present invention. On the other hand, if P is contained in excess, the oxidation resistance and the toughness of the hot-rolled sheet may deteriorate. Therefore, in one aspect of the present invention, the content of P is defined to be 0.050% or less. By setting the content of P to 0.040% or less, the deterioration of workability can be further reduced. In view of the above reasons, the more preferable content of P is 0.005 to 0.030%.
[0021] <S: Sulfur> S is an essential element in the ferritic stainless steel according to an embodiment of the present invention. On the other hand, if S is contained in excess, it may adversely affect the formation of the Al2O3 film in the ferritic stainless steel and deteriorate the oxidation resistance. Therefore, in one aspect of the present invention, the content of S is defined to be 0.005% or less. In view of the above reasons, the more preferable content of S is 0.0001 to 0.002%.
[0022] <Cr: Chromium> Cr is a basic alloying element necessary to improve the high-temperature oxidation resistance of ferritic stainless steel. By containing a predetermined amount or more of Cr, an oxide film is formed on the surface of the stainless steel, and the oxidation of the stainless steel is suppressed. On the other hand, if an excessive amount of Cr is contained, the toughness decreases and the manufacturability deteriorates. Therefore, in one aspect of the present invention, the content of Cr is defined to be 15.0 to 25.0%. By setting the content of Cr to 16.0 to 22.0%, more preferably 17.0 to 20.0%, the oxidation suppression effect and the manufacturability can be further improved.
[0023] <Al: Aluminum> Al is a basic alloying element necessary for improving the high-temperature oxidation resistance of ferritic stainless steel. By containing a predetermined amount or more of Al, an Al2O3 oxide film is formed on the surface of the stainless steel, suppressing the oxidation of the stainless steel. Further, when REM or Y is added, the oxide film becomes dense and the adhesion to the base steel is improved, suppressing the occurrence of abnormal oxidation. On the other hand, when Al is contained excessively, the toughness of the stainless steel deteriorates, and the manufacturability and workability deteriorate. Therefore, in one aspect of the present invention, the content of Al is defined to be 2.0 to 4.0%. By setting the content of Al to 2.5 to 3.7%, more preferably 2.8 to 3.5%, the high-temperature oxidation resistance and manufacturability can be further improved.
[0024] <Ni: Nickel> Ni is an element that improves the corrosion resistance of ferritic stainless steel and is an essential element in the ferritic stainless steel according to one embodiment of the present invention. On the other hand, when Ni is contained excessively, the ferrite phase becomes unstable and the material cost increases. Therefore, in one aspect of the present invention, the content of Ni is defined to be 1.00% or less. By setting the content of Ni to 0.50% or less, the destabilization of the ferrite phase due to excessive content and the increase in manufacturing cost can be further suppressed. In view of the above reasons, the more preferable content of Ni is 0.02 to 0.30%.
[0025] <N: Nitrogen> N is an essential element in the ferritic stainless steel according to one embodiment of the present invention. On the other hand, when contained excessively, it may combine with Al in the steel to form AlN, which may become a starting point for accelerated oxidation. Therefore, in one aspect of the present invention, the content of N is defined to be 0.030% or less. By setting the content of N to 0.025% or less, the possibility of hardening can be further reduced. In view of the above reasons, the more preferable content of N is 0.003 to 0.020%.
[0026] <Nb (Niobium), B (Boron), REM (Rare Earth Elements)> Nb is an element added to ensure high-temperature strength. In addition, Nb has the effect of promoting the formation of an Al2O3 film. It also suppresses recrystallization of stainless steel and increases the grain boundary area by refining the crystal grains. On the other hand, excessive Nb content may deteriorate the toughness of hot-rolled sheets.
[0027] B is an element that improves the secondary workability and oxidation resistance of molded products made from ferritic stainless steel. However, if there is an excessive amount of B, the B compounds become inclusions (impurities).
[0028] REM (rare earth metals) refers to lanthanoid elements (elements with atomic numbers 57 to 71, such as La, Ce, Pr, Nd, and Sm). REM is an element that improves high-temperature oxidation resistance. By containing a certain amount or more of REM, the aluminum oxide film is stabilized. In addition, oxidation resistance is improved by improving the adhesion between the base material and the oxide. On the other hand, excessive REM content causes surface defects during hot rolling, reducing manufacturability.
[0029] For the above reasons, in one embodiment of the present invention, the Nb content is specified to be 0.01 to 0.70%. By setting the Nb content to be 0.05 to 0.50%, more preferably 0.08 to 0.30%, the possibility of deterioration of workability can be further reduced and oxidation resistance can be improved. The upper limit of the Nb content is even more preferably 0.20% or 0.15%. In addition, the B content is specified to be 0.0003 to 0.01%. By setting the B content to be 0.0003 to 0.005%, the presence of inclusions can be further reduced and secondary workability can be improved. In addition, the REM content is specified to be 0.01 to 0.20%. The REM content is preferably 0.02 to 0.15%, more preferably 0.04 to 0.10%.
[0030] (Other Ingredients) The ferritic stainless steel according to one aspect of the present invention may further contain at least one element selected from Zr, V, Cu, Mo, W, Hf, Sn, Ta, Ti, Mg, and Ca as elements other than the above.
[0031] <Zr: Zirconium> Zr is an element that improves oxidation resistance. On the other hand, excessive addition of Zr may harden the steel and cause a decrease in toughness. Therefore, in one aspect of the present invention, it may contain 0.50% or less of Zr. Considering the reduction of hardening and the like, the content of Zr is more preferably 0.01 to 0.40%.
[0032] <V: Vanadium> V is an element that improves workability and toughness of the welded part. On the other hand, excessive addition of V may deteriorate the toughness of the hot-rolled sheet. In one aspect of the present invention, it may contain 0.50% or less of V. Considering the reduction of hardening and the like, the content of V is more preferably 0.02 to 0.35%.
[0033] <Cu: Copper> Cu is an element that improves the corrosion resistance of ferritic stainless steel. On the other hand, excessive content of Cu may cause a decrease in oxidation resistance and hot workability. Therefore, in one aspect of the present invention, it may contain 1.0% or less of Cu. Considering material costs and the like, the content of Cu is more preferably 0.01 to 0.5%.
[0034] <Mo: Molybdenum> Mo is an element that improves corrosion resistance. On the other hand, excessive content of Mo hardens, reduces toughness, and increases material costs. Therefore, in one aspect of the present invention, it may contain 2.0% or less of Mo. Considering workability, material costs, and the like, the content of Mo is more preferably 0.01 to 1.0%.
[0035] <W: Tungsten> W is an element added to ensure high-temperature strength. On the other hand, excessive W content deteriorates the hot-rolled sheet toughness and increases material costs. Therefore, in one embodiment of the present invention, W may be contained in an amount of 2.0% or less. In consideration of material costs, the W content is more preferably 0.01 to 1.0%.
[0036] <Hf:ハフニウム> Hf is an element that improves oxidation resistance. On the other hand, excessive Hf content reduces the toughness of the hot-rolled sheet and increases the material cost. Therefore, in one embodiment of the present invention, 0.50% or less of Hf may be contained. In consideration of toughness and material cost, the Hf content is more preferably 0.001 to 0.20%.
[0037] <Sn:スズ> Sn (tin) is an element that improves the corrosion resistance of ferritic stainless steel. On the other hand, if the content of Sn is excessive, the workability decreases and the material cost increases. Therefore, in one embodiment of the present invention, the content of Sn may be 0.50% or less. In consideration of the workability, the cost, etc., the content of Sn is more preferably 0.005 to 0.20%.
[0038] <Ta:タンタル> Ta is an element that improves the cleanliness and oxidation resistance of steel. On the other hand, excessive Ta content reduces toughness and increases material costs. Therefore, in one embodiment of the present invention, Ta may be contained in an amount of 0.5% or less. In consideration of toughness and material costs, the Ta content is preferably 0.40% or less. In view of the above reasons, the Ta content is more preferably 0.001 to 0.30%.
[0039] <Ti:チタン> Ti reacts with C and / or N to make the ferritic stainless steel into a ferritic single layer at 900 to 1000°C. On the other hand, excessive Ti content may generate TiO2 in the oxide of Al, which may deteriorate the oxidation life. Therefore, in one embodiment of the present invention, 0.20% or less of Ti may be contained. In consideration of workability, the Ti content is more preferably 0.005 to 0.15%.
[0040] <Mg:マグネシウム> Mg forms Mg oxide together with Al in molten steel and acts as a deoxidizer. On the other hand, excessive Mg content reduces the toughness of the steel and decreases manufacturability. Therefore, in one embodiment of the present invention, 0.015% or less of Mg may be contained. In view of the above reasons, the preferred Mg content is 0.0002 to 0.0080%.
[0041] <Ca:カルシウム> Ca is an element that improves hot workability. On the other hand, if Ca is contained in an excessive amount, the toughness of the steel decreases, and the manufacturability decreases. Therefore, in one embodiment of the present invention, Ca may be contained in an amount of 0.015% or less. In view of the above reasons, the preferred Ca content is 0.0001 to 0.012%.
[0042] The ferritic stainless steel in this embodiment may satisfy, when [Al] is the mass % of Al and [Nb] is the mass % of Nb, [Al] / (10×[Nb])<8. The inventors have found that a preferred amount of Nb is required according to the amount of Al added, and that by satisfying the above formula, various properties such as oxidation resistance shown in the examples described later can be satisfied.
[0043] (Al-based oxide film) Next, the Al-based oxide film on the surface of the ferritic stainless steel according to this embodiment will be described.
[0044] The ferritic stainless steel according to the present embodiment has an Al-based oxide film having a thickness of 8 nm or more and less than 20 nm on the surface. The Al-based oxide film is a film mainly composed of alumina, and is formed by a final annealing process described later. More specifically, the Al-based oxide film according to the present disclosure means a film having an Al concentration of 10% or more. By having an Al-based oxide film having a thickness of 8 nm or more, the ferritic stainless steel according to the present embodiment has oxidation resistance. In addition, by having an Al-based oxide film having a thickness of less than 20 nm, a ferritic stainless steel having excellent brazability can be realized.
[0045] (Alumina layer) As a result of intensive research, the present inventors have found that when ferritic stainless steel contains Nb and REM as essential elements in concentrations within the appropriate range, the columnar crystallization of the alumina layer formed under the conditions of use is improved. This is believed to be due to the concentration of Nb and REM at the grain boundaries of the alumina layer. They have also found that the columnar crystallization is improved by containing B as an essential element in a concentration within the appropriate range.
[0046] The ferritic stainless steel according to the present disclosure can be suitably applied to applications requiring oxidation resistance at high temperatures. Therefore, the above-mentioned use conditions refer to high-temperature conditions. For example, in this embodiment, the alumina layer 20 formed when heated at 1050°C for 50 hours is referred to.
[0047] The ferritic stainless steel according to this embodiment contains, by mass%, C: 0.030% or less, Si: 0.01 to 1.5%, Mn: 0.01 to 1.00%, P: 0.050% or less, S: 0.005% or less, Cr: 15.0 to 25.0%, Al: 2.0 to 4.0%, Ni: 1.00% or less, Nb: 0.01 to 0.70%, N: 0.030% or less, B: 0.0003 to 0.01%, and REM: 0.01 to 0.20%.
[0048] The alumina layer 20 formed by heating the ferritic stainless steel containing the above components at 1050°C for 50 hours has the following characteristics: That is, when (C) is the thickness of the columnar crystals in a cross section when the alumina layer 20 is cut in the thickness direction, and (E) is the thickness of the equiaxed crystals in a cross section when the alumina layer 20 is cut in the thickness direction, the following formula (1) is satisfied or the columnar crystals are 100%.
[0049] (C) / (E)≧1.2 (1) FIG. 1 is an SEM photograph showing a cross section of an alumina layer 20 mainly made of alumina, which is formed when a ferritic stainless steel 1 according to one embodiment of the present invention is heated at 1050° C. for 50 hours.
[0050] 1, when a ferritic stainless steel having an Al-based oxide film is heated at 1050° C. for 50 hours, an alumina layer 20 mainly made of alumina is formed in the ferritic stainless steel 1. The alumina layer 20 has columnar crystals 201 and equiaxed crystals 202.
[0051] The columnar crystals 201 are a structure in which crystal grains that have grown elongated in the thickness direction of the alumina layer 20 are arranged. The equiaxed crystals 202 are a polycrystalline structure in which the crystal grains that constitute the equiaxed crystals 202 are isotropic in shape and orientation. Reference C in Fig. 1 indicates the thickness of the columnar crystals in a cross section when the alumina layer 20 is cut in the thickness direction. Reference E in Fig. 1 indicates the thickness of the equiaxed crystals in a cross section when the alumina layer 20 is cut in the thickness direction.
[0052] The equiaxed crystals 202 have a higher grain boundary density than the columnar crystals 201, and therefore the number of grain boundary diffusion paths for oxygen increases. Therefore, the equiaxed crystals 202 have a shorter oxidation life than the columnar crystals 201. The ferritic stainless steel according to this embodiment has extremely excellent oxidation resistance under high temperature conditions, since the alumina layer 20 satisfies the above formula (1) or is 100% columnar crystals.
[0053] (Manufacturing method) First, an example of a manufacturing process of the ferritic stainless steel in this embodiment will be described briefly. The manufacturing process of the ferritic stainless steel in this embodiment includes a pretreatment process, a hot rolling process, an annealing process, a first pickling process, a cold rolling process, an intermediate annealing process, a final annealing process, and a second pickling process, in this order.
[0054] In the pretreatment step, first, a melting furnace in a vacuum or argon atmosphere is used to melt steel having a composition adjusted to fall within the range of the present invention, and the steel is cast to produce a slab. Then, a slab piece for hot rolling is cut out from the slab. Then, the slab piece is heated to a temperature range of 1100°C to 1300°C in an air atmosphere. The time for which the slab piece is heated and held is not limited. When the pretreatment step is carried out industrially, the casting may be continuous casting.
[0055] The hot rolling process is a process in which the slab (steel ingot) obtained in the pretreatment process is hot rolled to produce a hot rolled steel strip having a predetermined thickness.
[0056] The annealing step is a step for softening the hot-rolled steel strip obtained in the hot rolling step by heating the steel strip to, for example, 900 to 1050° C. This annealing step is a step that is performed as necessary, and does not necessarily have to be performed.
[0057] The first pickling step is a step of washing off scale adhering to the surface of the annealed steel strip obtained in the above annealing step with a pickling solution such as hydrochloric acid or a mixture of nitric acid and hydrofluoric acid.
[0058] The cold rolling step is a step in which the annealed steel strip from which the scale has been removed in the first pickling step is further rolled to a thinner strip. The rolling reduction in the cold rolling step is, for example, 50 to 90%.
[0059] The intermediate annealing step is a step for softening the steel strip obtained in the cold rolling step by heating the steel strip to, for example, 900 to 1050° C. This annealing step is a step that is performed as necessary, and does not necessarily have to be performed.
[0060] The method for producing ferritic stainless steel according to this embodiment includes a final annealing step after intermediate annealing (after cold rolling). In the final annealing step, a first step is performed in which the steel is heated to a temperature range of 900°C to 1200°C under conditions of an inert gas atmosphere with a dew point of -40°C or less. After the first step, a second step may be performed in which the steel is held at a temperature range of 900°C to 1200°C for 5 minutes or less under conditions of an inert gas atmosphere with a dew point of -40°C or less. The final annealing step allows the production of ferritic stainless steel having an Al-based oxide film having a thickness of 8 nm or more and less than 20 nm on the surface.
[0061] Here, the inert gas may be, for example, Ar, H2, or N2. Alternatively, the inert gas may be a mixture of two or three of Ar, H2, and N2 in the range of 1 to 99% each, making it 100%. More specifically, the inert gas may be, for example, a mixed gas of hydrogen, nitrogen, and / or argon, in which case it may contain 70 to 90% hydrogen and 10 to 30% nitrogen or argon, or it may contain 70 to 90% hydrogen and 5 to 25% nitrogen and argon so that the content of nitrogen and argon is 30%.
[0062] The second pickling step is a step in which, as necessary, scale adhering to the surface of the steel strip obtained in the final annealing step is washed off using a pickling solution such as a mixture of nitric acid and hydrofluoric acid.
[0063] (summary) The ferritic stainless steel according to embodiment 1 of the present disclosure contains, by mass%, C: 0.030% or less, Si: 0.01 to 1.5%, Mn: 0.01 to 1.00%, P: 0.050% or less, S: 0.005% or less, Cr: 15.0 to 25.0%, Al: 2.0 to 4.0%, Ni: 1.00% or less, Nb: 0.01 to 0.70%, N: 0.030% or less, B: 0.0003 to 0.01%, REM: 0.01 to 0.20%, with the remainder being Fe and unavoidable impurities, and has an Al-based oxide film of 8 nm or more and less than 20 nm on the surface.
[0064] According to the above-mentioned configuration, a ferritic stainless steel having excellent oxidation resistance and brazability can be realized.
[0065] The ferritic stainless steel according to aspect 2 of the present disclosure, in the above-mentioned aspect 1, forms an alumina layer mainly composed of alumina when heated at 1050°C for 50 hours, and the alumina layer may satisfy the following formula (1) or be 100% columnar crystals, where (C) is the thickness of columnar crystals 201 in a cross section when the alumina layer 20 is cut in the thickness direction, and (E) is the thickness of equiaxed crystals 202 in a cross section when the alumina layer 20 is cut in the thickness direction.
[0066] (C) / (E)≧1.2 (1) According to the above-mentioned configuration, it is possible to realize a ferritic stainless steel having excellent oxidation resistance under high temperature conditions. In particular, when the alumina layer is 100% columnar crystals, it is possible to realize a ferritic stainless steel having even more excellent oxidation resistance.
[0067] The ferritic stainless steel according to aspect 3 of the present disclosure, in accordance with aspect 1 or 2 above, may further contain, by mass%, one or more of Zr: 0.50% or less, V: 0.50% or less, Cu: 1.0% or less, Mo: 2.0% or less, W: 2.0% or less, Hf: 0.50% or less, Sn: 0.50% or less, Ta: 0.5% or less, Ti: 0.20% or less, Mg: 0.015% or less, and Ca: 0.015% or less. A ferritic stainless steel according to a fourth aspect of the present disclosure is any one of the first to third aspects, in which, when [Al] is the mass% of Al and [Nb] is the mass% of Nb, [Al] / (10×[Nb])<8 may be satisfied.
[0068] A method for producing a ferritic stainless steel according to a fifth aspect of the present disclosure is a method for producing a ferritic stainless steel containing, by mass%, C: 0.030% or less, Si: 0.01 to 1.5%, Mn: 0.01 to 1.00%, P: 0.050% or less, S: 0.005% or less, Cr: 15.0 to 25.0%, Al: 2.0 to 4.0%, Ni: 1.00% or less, Nb: 0.01 to 0.70%, N: 0.030% or less, B: 0.0003 to 0.01%, REM: 0.01 to 0.20%, and the balance being Fe and unavoidable impurities, The final annealing step after the cold rolling step includes a first step of heating to a temperature range of 900°C to 1200°C under an inert gas atmosphere with a dew point of -40°C or lower.
[0069] According to the above-mentioned method, it is possible to produce a ferritic stainless steel having an Al-based oxide film having a thickness of 8 nm or more and less than 20 nm on the surface, thereby making it possible to produce a ferritic stainless steel having excellent oxidation resistance and brazability.
[0070] In the method for producing a ferritic stainless steel according to aspect 6 of the present disclosure, in aspect 5 above, the final annealing step may include a second step, after the first step, of holding the steel at a temperature in the range of 900°C to 1200°C for 5 minutes or less.
[0071] According to the above-mentioned method, it is possible to produce a ferritic stainless steel having an Al-based oxide film having a thickness of 8 nm or more and less than 20 nm on the surface.
[0072] A method for producing a ferritic stainless steel according to aspect 7 of the present disclosure is such that, in aspect 5 or 6 above, the ferritic stainless steel obtained through the final annealing step forms an alumina layer mainly composed of alumina when heated at 1050°C for 50 hours, and the alumina layer satisfies the following formula (1) or may be 100% columnar crystals, where (C) is the thickness of columnar crystals 201 in a cross section when the alumina layer is cut in the thickness direction, and (E) is the thickness of equiaxed crystals 202 in a cross section when the alumina layer 20 is cut in the thickness direction. (C) / (E)≧1.2 (1)
[0073] According to the above-mentioned configuration, it is possible to realize a ferritic stainless steel having excellent oxidation resistance under high temperature conditions. In particular, when the alumina layer is 100% columnar crystal, it is possible to realize a ferritic stainless steel having brazeability and excellent oxidation resistance. A method for producing a ferritic stainless steel according to aspect 8 of the present disclosure is any one of aspects 5 to 7 above, wherein the ferritic stainless steel may further contain, by mass%, one or more of Zr: 0.50% or less, V: 0.50% or less, Cu: 1.0% or less, Mo: 2.0% or less, W: 2.0% or less, Hf: 0.50% or less, Sn: 0.50% or less, Ta: 0.5% or less, Ti: 0.20% or less, Mg: 0.015% or less, and Ca: 0.015% or less.
[0074] [Example] In order to evaluate the physical properties of the ferritic stainless steel of the present invention, ferritic stainless steels were produced as example steels and comparative steels using the components shown in Table 1 below. In Table 1, steel types No. 1 to 16 are ferritic stainless steels as examples of the present invention produced within the scope of the present invention. Also in Table 1, steel types No. 17 to 27 are ferritic stainless steels as comparative examples produced under conditions outside the scope of the present invention.
[0075] In producing the steel materials of the steel types shown in Table 1, first, steels having the components shown in Table 1 were vacuum melted to produce 30 kg slabs. The slabs were heated at 1230°C for 2 hours and then hot rolled to produce hot-rolled sheets with a thickness of 3 mm. The obtained hot-rolled sheets were annealed between 900 and 1050°C to produce hot-rolled annealed sheets. The obtained hot-rolled annealed sheets were subjected to cold rolling and intermediate annealing three times each to produce cold-rolled sheets with a thickness of 50 μm. The obtained cold-rolled sheets were subjected to final annealing under an inert gas atmosphere under the conditions of temperature, time, and dew point shown in Table 2. Steel types No. 1 to 27 were subjected to final annealing using a gas containing 70 to 90% H2 and 10 to 30% N2 or Ar as the inert gas.
[0076] The cold rolling was performed at a rolling ratio of 60 to 85%, and intermediate annealing after the cold rolling was performed in a temperature range of 900 to 1050° C. The manufacturing method described in this embodiment is merely an example, and is not intended to limit the manufacturing method. [Table 1] [Table 2] Table 1 shows the composition of the components contained in each steel grade in mass %. The remainder other than the components shown in Table 1 is Fe or small amounts of impurities that are inevitably mixed in (unavoidable impurities). The underlines in Table 1 indicate that the range of each component contained in each stainless steel according to the comparative example of the present invention is outside the range of the present invention.
[0077] (Measurement of film thickness) The thicknesses of the Al-based oxide films produced under the conditions shown in Tables 1 and 2 in the examples of the present invention and the comparative examples will be described below.
[0078] The thickness of the Al-based oxide film was measured using a glow discharge spectroscopy (GDS) (GD-Profiler2 manufactured by HORIBA). Specifically, the Al concentration was measured at 0.0025 μm pitch from the surface to a depth of 0.1 μm for the cold-rolled annealed sheets having a thickness of 50 μm according to the present invention and the comparative examples. The measurement conditions for the GDS measurement were gas replacement time: 200 seconds, pre-sputtering time: 30 seconds, background: 5 seconds, depth: 1.01 μm, pressure: 600 Pa, power: 35 W, and effective value: 8.75 W. Module: 8 V, phase: 4 V, frequency: 100 Hz, and duty cycle: 0.25.
[0079] The thickness of the alumina-based coating was determined as the half-value width of the oxygen peak concentration. The results are shown in Table 2 below. In the evaluation of the alumina-based coating in Table 2, "good" (◯) indicates that the alumina-based coating was less than 20 nm thick, and "poor" (×) indicates that the alumina-based coating was 20 nm thick or more.
[0080] (Brazability evaluation test) The brazeability evaluation test carried out on the present invention examples and comparative examples shown in Tables 1 and 2 will be described below. The brazeability evaluation test was carried out by preparing JIS 13B test pieces from cold-rolled annealed sheets with a thickness of 50 μm, and then cutting them in half. Specifically, the half-cut samples were overlapped by 10 mm, and a brazing material (BNi-5: ASTM) was applied to one of the contact surfaces (12.5 mm x 10 mm) to a thickness of 0.1 mm. Then, using an atmospheric heat treatment furnace, the overlapped samples were brazed at 1200 ° C in a vacuum (dew point -65 ° C) and joined. After joining, a tensile test was carried out. The values shown in Table 3 indicate the tensile strength (MPa) at the time when the fracture occurred. When the tensile strength was 250 MPa or more, the brazeability was judged to be good. Also, when the fracture occurred from the base material in the tensile test, the brazeability was judged to be good. On the other hand, when the fracture occurred from the brazed part, the brazeability was judged to be poor. Those having good brazeability are indicated as "◯ (good)" in Table 3. Those having poor brazeability are indicated as "× (poor)" in Table 3.
[0081] (Measurement of columnar / equixed crystal ratio of alumina layer mainly composed of alumina) The following describes the measurement of the columnar / equixized crystal ratio of the alumina layer, which was carried out for the present invention examples and comparative examples shown in Tables 1 and 2. First, the test piece was heated at 1050°C for 50 hours, immersed in liquid nitrogen for 5 minutes, removed, and immediately subjected to impact to break it. Then, using a scanning electron microscope (SEM) SU5000 (manufactured by Hitachi High-Tech Corporation), the cross section of the alumina layer was observed at a magnification of 20,000 times, and the thickness of the columnar crystals (C) and the thickness of the equiaxed crystals (E) were measured to calculate the columnar / equixized crystal ratio ((C) / (E)).
[0082] The columnar / equixized crystal ratio was measured by SEM observation at 20,000 times magnification, and the average value was calculated from measurements taken at three random locations. When the equiaxed crystals were not formed in layers, the length of the equiaxed crystal grains that existed independently was determined as the thickness of the equiaxed crystals.
[0083] The results are shown in Table 3. In the evaluation of the columnar / equixized crystal ratio of the alumina layer in Table 2, "good" (◯) indicates that the columnar / equixized crystal ratio of the alumina layer is 1.2 or more, and "poor" (×) indicates that the columnar / equixized crystal ratio of the alumina layer is less than 1.2.
[0084] (High-temperature oxidation resistance evaluation test) The following describes the high-temperature oxidation resistance evaluation test carried out on the examples of the present invention and the comparative examples shown in Tables 1 and 2. First, for each steel type shown in Table 1, three test pieces, each 20 mm wide and 25 mm long, were taken from a cold-rolled sheet with a thickness of 50 μm as described in the manufacturing of the steel material. The test pieces were exposed to an air atmosphere at 1,050°C for 50 hours, and the average oxidation weight gain of the three pieces was measured. This high-temperature oxidation resistance evaluation test was carried out in air using an EREMA electric furnace. The results are shown in Table 3 below. In the judgment of high-temperature oxidation resistance in Table 3, "good" indicates an average oxidation gain of 1 mg / cm 2 or less, and "× (defective)" is 1 mg / cm 2 This indicates that it exceeded the [Table 3] As shown in the column for Al-based oxide film thickness in Table 3, all of the example steels No. 1 to 16 manufactured according to the manufacturing method within the scope of the present invention had an Al-based oxide film thickness of less than 20 nm and had good brazability.
[0085] In contrast, the comparative steel types Nos. 17 to 18, 21, 23, and 25 to 27 had an Al-based oxide film with a thickness of 20 nm or more, and had poor brazeability.
[0086] Furthermore, the results in the column for Al-based oxide film thickness in Table 3 demonstrate that ferritic stainless steels having an Al-based oxide film thickness of less than 20 nm have excellent brazeability.
[0087] Furthermore, as shown in the column of oxidation resistance results in Table 3, it was demonstrated that all of the example steels No. 1 to 16, which were heated at 1050° C. for 50 hours in the final annealing process, exhibited good oxidation resistance.
[0088] Furthermore, the results of the columnar crystal / equixized crystal ratio and the results of the oxidation resistance in Table 3 demonstrate that when the columnar crystal / equixized crystal ratio is 1.2 or more, high-temperature oxidation resistance is good.
[0089] That is, it was demonstrated that when the ferritic stainless steel within the range of the present invention was heated at 1050° C. for 50 hours, it had excellent brazeability and oxidation resistance.
[0090] The reason why the comparative steels No. 17 to 27 do not show better results than the inventive steels will be explained below.
[0091] Comparative steel No. 17 had a Mn content of more than 1.0%, which resulted in a decrease in high-temperature oxidation resistance, and a B content of less than 0.0003%, which not only reduced secondary workability but also did not show good brazability.
[0092] Comparative steel No. 18 did not show excellent high-temperature oxidation resistance because the REM content was less than 0.01% and the Ti content was more than 0.20%, which made it prone to equiaxed crystallization.
[0093] Comparative steel No. 19 did not show excellent high-temperature oxidation resistance because the Nb content was less than 0.01%, which may cause deterioration in high-temperature oxidation resistance and workability. On the other hand, comparative steel No. 19 showed good brazeability because the Ti content was less than 0.20%.
[0094] Comparative steel No. 20 did not contain Ti and was therefore less likely to form Ti-based oxides, and therefore showed good brazability results. On the other hand, comparative steel No. 20 contained more than 0.50% Zr, which led to the segregation of Zr at the alumina grain boundaries and promoted the formation of equiaxed crystals.
[0095] Comparative steel No. 21 had a Si content of more than 1.5%, and exhibited excellent high-temperature oxidation resistance due to the effects of Si-based oxides such as SiO2. In contrast, comparative steel No. 21 had a Si content of more than 1.5%, and exhibited poor brazeability due to the formation of Si-based oxides.
[0096] Comparative steel No. 22 had an Al content lower than 2.0%, and was therefore less likely to form an oxide film of Al2O3. Therefore, while it showed good results in terms of brazeability, it did not show good results in terms of high-temperature oxidation resistance.
[0097] Comparative steel No. 23 had a Ti content higher than 0.20%, and therefore Ti oxides such as TiO2 were formed, and therefore did not show good results in terms of high-temperature oxidation resistance and brazeability.
[0098] Comparative steel No. 24 had a Nb content higher than 0.70% and was prone to equiaxed crystallization, and therefore did not show good results in terms of high-temperature oxidation resistance.
[0099] Comparative steel No. 25 has an Al content higher than 4.0% and is prone to forming an oxide film of Al2O3. Therefore, while it showed good results in terms of high-temperature oxidation resistance, it did not show good results in terms of brazability.
[0100] Comparative steel No. 26 has a Cr content higher than 25.0%, which causes Cr to concentrate at the alumina grain boundaries and tends to form equiaxed crystals. Comparative steel No. 26 also has a Ti content higher than 0.20%, which causes Ti oxides such as TiO2 to form. For this reason, Comparative steel No. 26 did not show good results in terms of high-temperature oxidation resistance and brazeability.
[0101] Comparative steel No. 27 showed good results in terms of high-temperature oxidation resistance because the REM content was greater than 0.20%, but did not show good results in terms of brazeability because the REM content was greater than 0.20%, which resulted in the formation of oxides such as Y2O3 or CeO2.
[0102] (Additional Notes) The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention. [Explanation of symbols]
[0103] 1 Ferritic stainless steel 20 Alumina layer 201 Columnar crystals 202 Equiaxed crystal C Columnar crystal thickness E thickness of equiaxed grain
Claims
1. A ferritic stainless steel containing, by mass%, C: 0.030% or less, Si: 0.01 to 1.5%, Mn: 0.01 to 1.00%, P: 0.050% or less, S: 0.005% or less, Cr: 15.0 to 25.0%, Al: 2.0 to 4.0%, Ni: 1.00% or less, Nb: 0.01 to 0.70%, N: 0.030% or less, B: 0.0003 to 0.01%, REM: 0.01 to 0.20%, with the balance being Fe and unavoidable impurities, and having an Al-based oxide film of 8 nm or more and less than 20 nm on the surface.
2. When heated at 1050° C. for 50 hours, an alumina layer mainly made of alumina is formed. The alumina layer has a thickness of columnar crystals in a cross section of the alumina layer cut in the thickness direction, and a thickness of equiaxed crystals in a cross section of the alumina layer cut in the thickness direction, and the thickness of the columnar crystals in the cross section of the alumina layer cut in the thickness direction is expressed by the following formula (1): (C) / (E)≧1.2...(1) 2. The ferritic stainless steel according to claim 1, wherein said ferritic stainless steel satisfies the above or has 100% columnar grains.
3. 3. The ferritic stainless steel according to claim 1 or 2, further containing, by mass%, one or more of Zr: 0.50% or less, V: 0.50% or less, Cu: 1.0% or less, Mo: 2.0% or less, W: 2.0% or less, Hf: 0.50% or less, Sn: 0.50% or less, Ta: 0.5% or less, Ti: 0.20% or less, Mg: 0.015% or less, and Ca: 0.015% or less.
4. When [Al] is the mass% of Al and [Nb] is the mass% of Nb, The ferritic stainless steel according to claim 1 or 2, wherein [Al] / (10×[Nb])<8 is satisfied.
5. A method for producing a ferritic stainless steel containing, by mass%, C: 0.030% or less, Si: 0.01 to 1.5%, Mn: 0.01 to 1.00%, P: 0.050% or less, S: 0.005% or less, Cr: 15.0 to 25.0%, Al: 2.0 to 4.0%, Ni: 1.00% or less, Nb: 0.01 to 0.70%, N: 0.030% or less, B: 0.0003 to 0.01%, REM: 0.01 to 0.20%, and the balance being Fe and unavoidable impurities, A cold rolling step and a final annealing step after the cold rolling step, The method for producing ferritic stainless steel, wherein the final annealing step includes a first step of heating the steel to a temperature range of 900°C to 1200°C in an inert gas atmosphere under conditions of a dew point of -40°C or lower.
6. The method for producing a ferritic stainless steel according to claim 5, wherein the final annealing step includes a second step of holding the steel at a temperature in the range of 900°C to 1200°C for 5 minutes or less after the first step.
7. The ferritic stainless steel obtained through the final annealing step is When heated at 1050° C. for 50 hours, an alumina layer mainly made of alumina is formed. When (C) is the thickness of columnar crystals in a cross section when the alumina layer is cut in the thickness direction, and (E) is the thickness of equiaxed crystals in a cross section when the alumina layer is cut in the thickness direction, the alumina layer has a thickness satisfying the following formula (1): (C) / (E)≧1.2...(1) 7. The method for producing a ferritic stainless steel according to claim 5 or 6, wherein the above-mentioned condition is satisfied or the columnar grains are 100%.
8. The method for producing a ferritic stainless steel according to claim 5 or 6, wherein the ferritic stainless steel further contains, by mass%, one or more of Zr: 0.50% or less, V: 0.50% or less, Cu: 1.0% or less, Mo: 2.0% or less, W: 2.0% or less, Hf: 0.50% or less, Sn: 0.50% or less, Ta: 0.5% or less, Ti: 0.20% or less, Mg: 0.015% or less, and Ca: 0.015% or less.
Citation Information
Patent Citations
Fe-Cr-Al BASED ALLOY FOIL HAVING EXCELLENT OXIDATION RESISTANCE AND HIGH TEMPERATURE DEFORMATION RESISTANCE, AND PRODUCTION METHOD THEREFOR
JP2003105506A
Stainless steel foil and method for producing the same
JP2011032524A
Stainless steel
JP2021004384A
Ferritic stainless steel
JP2021055141A
Ferritic stainless steel sheet and welded structure
JP2021161470A